Penerapan Dynamic Governance terhadap Tata Kelola Permukiman Akibat Dampak Urbanisasi di Kota Depok Tahun 2022 - Yanuar, Ferdy; Sri Kartini, Dede; Akbar, Idil (Universitas Indo Global Mandiri, 2023)
Urbanization is a dynamic phenomenon, where the population lock-in that occurs is triggered by the large number of economic centers in urban areas, especially in the JABODETABEK area. However, in reality Depok City, which is one of these satellite cities, has not been able to overcome the impact of increasing urbanization on plantation management. Dealing with plantation governance in responding to urbanization challenges in Depok City is the focus of the Depok City Regional Development Planning Agency (BAPPEDA), the Depok City Housing and Settlement Service (Disrumkim), the Depok City Public Works and Spatial Planning Office (DPUPR), and other institutions. . This study discusses the dynamics of the Depok City Government in implementing governance management to deal with the impacts of urbanization such as the rise of uninhabitable, obsolete, slum, liars, and so on. In addition, the concept of Dynamic Governance System put forward by Boon Siong Neo and Geraldine Chen in 2007 was used to analyze this research. The results of this study found that the handling carried out by the Depok City Government regarding these problems resulted in positive changes. So that adaptive policies can be created, such as setting simple subsidized house prices that are adjusted to the income of urbanites by making binding regulations, as well as other adaptive policy suggestions put forward in this study on elements of change.